(untitled) (Journal of Natural Language and Linguistics, 2024)
This study explores the complexities surrounding cultural stereotypes and bias within the Indonesian tertiary English Language Teaching/English as a Foreign Language (ELT/EFL) classrooms. Recognizing culture as a dynamic amalgamation of beliefs, values, and practices, it underscores its pivotal role in language acquisition. Employing a descriptive qualitative approach, the research utilizes semi-structured questionnaires and in-depth interviews to capture educators’ and students’ lived experiences, perceptions, and attitudes. The findings illuminate a shared acknowledgment of the significance of divulging personal information to counter cultural stereotypes, albeit with divergent viewpoints. Despite encountering obstacles, participants have tangible awareness regarding cultural biases within the educational setting, with the integration of diverse materials emerging as a perceived effective strategy. The study underscores the acknowledged difficulty in tackling cultural stereotypes but underscores the confidence in educators’ abilities to actively implement strategies. Moreover, teacher responsiveness to student feedback on cultural inclusivity is viewed as constructive. It duly recognizes the impact of cultural stereotypes on the learning environment and advocates for inclusive and culturally sensitive educational approaches. In conclusion, the research advocates for proactive measures to address cultural biases, promoting inclusivity and sensitivity within Indonesian tertiary ELT/EFL classrooms.